2003
DOI: 10.1787/eco_studies-v2001-art6-en
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, market structure and performance in air passenger transportation

Abstract: The paper uses a data base on regulation, market structure and performance in the air passenger transportation industry, to analyse the links among liberalisation, private ownership, competition, efficiency and airfares at national and route levels. Covering the 1996-97 travel season, 21 aggregate indicators have been developed for 27 OECD countries, and 23 micro indicators for 102 air routes connecting 14 major international airports. These data are summarised by means of factor analysis. Controlling for mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
5
0
2
Order By: Relevance
“…This is also confirmed by a number of cross-country studies on the short-run effects of reforms and on their effects on specific sectors (e.g. Bouis et al, 2012;Boylaud et al, 2001;Steiner, 2001;and Gönenç and Nicoletti, 2001).…”
supporting
confidence: 58%
“…This is also confirmed by a number of cross-country studies on the short-run effects of reforms and on their effects on specific sectors (e.g. Bouis et al, 2012;Boylaud et al, 2001;Steiner, 2001;and Gönenç and Nicoletti, 2001).…”
supporting
confidence: 58%
“…Market access in the provision of cross-border air services is traditionally determined by bilateral agreements that may regulate the number and nationality of airlines, route capacities and prices. A number of studies have shown that additional entry and relaxation of capacity restrictions is generally associated with lower prices, greater economies of scale and scope, and increased welfare (see, for example, Dresner and Tretheway, 1992;Gönenç and Nicoletti, 2001). Unfortunately, we could not find any empirical study that analyzed the effect of bilateral open skies agreements on third countries.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque ésta sea la realidad para el sector, la constante creación e inmersión de aerolíneas de bajo costo, es un factor preocupante por la competencia de mercado que se genera (Candela, 2008), no obstante, Gönenç y Nicoletti (2001) y Armstrong y Sappington (2006) hablan sobre servicios adicionales como mayor valor agregado.…”
Section: Ii1 Panorama Actual Del Sectorunclassified